Factor mobility and fiscal policy in the EU: policy issues and analytical approaches - David E. Wildasin (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paper outlines some of the implications of factor market integration for fiscal policy in the countries of the EU and for the EU itself. It draws particular attention to the dynamic dimensions of factor market integration, and identifies some of the many issues for further research on these topics. The past century has seen dramatic growth in the role of the public sector in the countries of Western Europe, both by extensive regulatory as well as fiscal interventions. By far the most important reason for the growth of public spending has been the increase in the level of redistributive (or social insurance) activities of governments. These include public pension systems and health care programs as well as a host of other policies. Tax policies also have the e ect of redistributing income among different groups. European economic integration, including prospective enlargement of the EU, contributes to the freer movement of factors of production, such as labor and capital, both within the EU and between the EU and neighboring regions. Integration of factor markets affects the distribution of income and factor movements depend on fiscal incentives, affecting the benefits and costs of redistributive policies. The paper begins by recapitulating some of the basic principles that have emerged from the existing literature on fiscal competition. It then describes recent trends in international migration and capital movements. The evidence suggests that the countries of Europe are experiencing inter-regional movements of labor and capital of significant magnitude, but that these movements are far from instantaneous. Labor and capital markets are clearly linked across regions, but there appear to be obstacles to very rapid adjustments of labor and capital stocks, suggesting that labor and capital are mobile but imperfectly so. The analysis of factor mobility with explicit dynamics thus offers promise. Different types of "stock adjustment" models of labor and capital mobility have important implications for the analysis of the distributional and allocative effects of fiscal policy. A formal analysis of fiscal competition with integrated capital markets and explicit costs of adjustment for the capital stock shows that sluggish capital adjustment creates incentives for governments to use tax policy to capture quasi-rents for their residents, even if it is impossible for any one government to impose net fiscal burdens on capital that is perfectly mobile in the long run.
Keywords: 330; Faktormobilität; Finanzpolitik; Sozialstaat; Steuerwettbewerb; Internationale Kapitalmobilität; Internationale Arbeitsmobilität; EU-Staaten